COVID-19 post-implications for sustainable banking sector performance: evidence from emerging Asian economies. Issue 1 (31st December 2022) - Xie, Haijuan; Chang, Hsu-Ling; Hafeez, Muhammad; Saliba, Chafic
Abstract: The novel COVID-19 virus, and the pandemic that has followed its spread, has had a massive impact on the banking industry on a global level. Therefore, considering this context, this study examines the effect of the COVID-19 pandemic on the banking sector's performance in the Asian emerging economics, over a time span ranging from 2016Q1–2021Q2. For this purpose, this study makes use of the FE, RE, 2SLS, and PPML regression models. The empirical findings show that the GDP and banking size are positively related to bank performance in the pre-COVID era, and the COVID pandemics era thus far in the Asian emerging economies. In addition to this, the findings also reveal that the impact of GDP and bank size on banking performance is lower in the pandemic period, as compared to the pre-COVID period. Furthermore, the results show that the COVID pandemic has significantly affected the banking sector performance in the Asian emerging economies. Findings have also suggested that the central bank should shift their focus on the banking industry in the Asian emerging economies. Various other policy implications have also been suggested under the present study.